Leptin deficiency in CD8+ T cells ameliorates non-segmental vitiligo by reducing interferon-γ and Granzyme B - Wu, Meiyu; Wang, Lu; Wu, Haijing; Yang, Ming; He, Zhenghao; Chen, Yiran; Zhang, Huiming (Frontiers in Immunology, 2023)
Background: Vitiligo is an autoimmune skin disease mainly mediated by CD8+ T cells, which affects about 0.1%-2% population of the world. Leptin plays a critical role in regulating the activation of CD8+ T cells. However, the effect of Leptin on vitiligo remains unclear. Objectives: To explore the effect of leptin on CD8+ T cells and its influence on vitiligo. Methods: RNA sequencing and Quantitative Real-time PCR (RT-qPCR) were used to explore the differentially expressed genes. Immunofluorescence staining was performed on skin lesions. Leptin in serum was detected by enzyme linked immunosorbent assay (ELISA). The peripheral blood mononuclear cells were detected by flow cytometry after leptin stimulation for 72 hours. A vitiligo model was established by monobenzone on Leptin KO mice. Results: 557 differentially expressed genes were found, including 154 up-regulated and 403 down-regulated genes. Lipid metabolism pathways showed a close relationship to the pathogenesis of vitiligo, especially the PPAR signaling pathway. RT-qPCR (p = 0.013) and immunofluorescence staining (p = 0.0053) verified that LEPR expressed significantly higher in vitiligo. The serum leptin level of vitiligo patients was significantly lower than that of healthy controls (p = 0.0245). The interferon-γ subset of CD8+LEPR+ T cells from vitiligo patients was significantly higher (p = 0.0189). The protein level of interferon-γ was significantly increased after leptin stimulation in vitro (p = 0.0217). In mice, Leptin deficiency resulted in less severe hair depigmentation. Leptin deficiency also resulted in significantly lower expressed vitiligo-related genes, such as Cxcl9 (p = 0.0497), Gzmb (p < 0.001), Ifng (p = 0.0159), and Mx1 (p < 0.001) after modeling. Conclusions: Leptin could promote the progression of vitiligo by enhancing the cytotoxic function of CD8+ T cells. Leptin may become a new target for vitiligo treatment.